Carbon Nanomaterials in the Treatment of Infectious Bone Defects and Wound Scars after Wushu Fractures - Shenghui Wei; Lei Zou; Xu Hu; Qiuming Li (Journal of Chemistry)
Although modern antibiotics and surgical technology have made great progress, when using carbon nanomaterials to treat bone marrow-induced inflammation after martial arts fractures, how to simultaneously repair bone defects and control wound infections is the current focus of orthopedics research. This paper uses electrospinning technology to develop a carbon nanomaterial based on PLA, HA-g-PLA, and vancomycin. The surface morphology, biocompatibility, drug release, and osteogenesis of carbon nanomaterials are studied, selecting animal models to verify its effect in the treatment of osteomyelitis with bone defects and provide new ideas and new methods for the treatment of bone defects complicated by osteomyelitis infection. In this paper, carbon nanofibers containing doxycycline, a small molecule protease inhibitor, were prepared by simple blending. Encapsulation of carbon nanofibers can control the slow release of doxycycline and improve the effect of doxycycline in treating chronic wounds. This article uses two methods to prepare different types of osteomyelitis models and compare them. After injecting saline or bacterial solution, the two groups were sealed with bone wax and the incision was closed; the blank group did not do any treatment. Within 30 days after surgery, the appearance of the left hind limb wound and general signs of infection were closely monitored, body temperature was measured, and blood was collected from the ear veins of experimental animals to analyze the changes in C-reactive protein (CRP) and procalcitonin levels (PCT); X-ray, CT imaging, and histological observation were performed on 14 and 28 days. Studies have shown that when the drug loading of doxycycline increases from 10% to 15%, this is related to the change in properties of the polylactic acid fiber membrane from hydrophobic to hydrophilic caused by the increase in doxycycline drug loading.